Diagnosing and Managing Intestinal Ascariasis in Vulnerable Communities - Syahruddin, Febie Irsandy (Fakultas Ilmu Kesehatan, 2025)
Ascariasis caused by Ascaris lumbricoides, remains one of the most prevalent parasitic infections globally, particularly in developing regions with poor sanitation. This review focuses on the diagnosis and management of intestinal ascariasis in vulnerable communities, where the burden of the disease is disproportionately high. Despite advances in diagnostic tools, such as ultrasonography, which provides a non-invasive, rapid, and effective modality for identifying intestinal worms, significant challenges persist in these regions due to limited healthcare infrastructure and socioeconomic constraints. lumbricoides highlights the need for prompt diagnosis and intervention, as delays can result in complications like gastrointestinal obstruction and systemic health deterioration. Ultrasonographic findings, such as tubular structures with echogenic features and anechoic canals, have proven reliable for early detection. Case studies, such as pediatric patients from underserved areas, underscore the importance of integrating advanced diagnostic approaches into primary care settings. Effective management includes anthelmintic therapy.